Testosterone Plasma Concentration is Associated with Insulin Resistance in Male Hypertensive Patients - Schianca, Gian Piero Carnevale; Fra, Gian Paolo; Brustia, Fabio; Bellan, Mattia; Pirovano, Alice; Gualerzi, Alessandro; Gentile, Michela; Gibbin, Antonello; Menegatti, Mirta; Bartoli, Ettore; Pirisi, Mario (Experimental and Clinical Endocrinology & Diabetes, 2017)
Background: Low testosterone levels are a common finding among men with Type 2 Diabetes Mellitus (T2DM) and are inversely related to insulin resistance. Whether this relationship holds true in patients with hypertension, but normal glucose tolerance or prediabetes, is unclear.Methods: We recruited 87 male outpatients with essential arterial hypertension, aged 35–70 years. Anthropometric data were collected, an Oral Glucose Tolerance Test (OGTT) performed, and the homeostasis model assessment of insulin resistance (HOMA-IR) score calculated. Follicle-Stimulating Hormone, Luteinizing Hormone, testosterone, Sex Hormone-Binding-Globulin and free-testosterone were measured. The concentrations of sex hormones were compared between normoglucotolerant, prediabetic and diabetic patients. Non-parametric tests were applied as appropriate to verify differences among groups, while multiple linear regression was used to predict the variability of testosterone and free-testosterone.Results: Total serum testosterone concentration was significantly lower in T2DM in comparison to normoglucotolerant subjects (p<0.01) and was inversely related to body mass index (r=− 0.25, p<0.01), waist circumference (r=− 0.27, p<0.01), pre and post-OGTT plasma glucose (r=− 0.4, p<0.0001 and r=− 0.29, p<0.01, respectively), pre and post-OGTT plasma insulin (r=− 0.42, p<0.0001 and r=− 0.42, p<0.0001) and HOMA-IR (r=− 0.46, p<0.0001). Similar associations were observed for free testosterone; HOMA-IR was related to testosterone and free-testosterone even in patients with normal glucose tolerance (r=− 0.47, p<0.01 and r=− 0.34, p<0.05, respectively). At multivariate analysis HOMA-IR was the only variable associated to testosterone (p<0.001) and free-testosterone (p<0.05) plasma concentration.Conclusions: In males with hypertension, the link between insulin sensitivity and hypothalamic-pituitary-gonadal axis is maintained along the entire spectrum of glucose tolerance.
Keywords: diabetes mellitus; testosterone; oral glucose tolerance test; hypogonadism